Poor Places, Thriving People : How the Middle East and North Africa Can Rise above Spatial Disparities. (MENA development report., 2011)
Geographical differences in living standards are a pressing concern for policy makers in the Middle East and North Africa (MENA) region. Production is most efficient when concentrated in leading areas. So how can the region reduce spatial disparities in well-being without compromising growth? Poor Places, Thriving People addresses this compelling issue.